1999
DOI: 10.7863/jum.1999.18.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section scar as a cause of abnormal vaginal bleeding: diagnosis by sonohysterography.

Abstract: A previously undescribed cause of abnormal uterine bleeding is presented. Nine of 310 women evaluated by sonohysterography for abnormal bleeding demonstrated an 8 to 17 mm gap in the anterior lower uterine segment myometrium at the site of prior cesarean deliveries. All women were premenopausal and had a history of 2 to 12 days of postmenstrual spotting. Presumably a lack of coordinated muscular contractions occurs around the cesarean scar, allowing the defect to collect menstrual debris. Subsequently, the deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
130
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(139 citation statements)
references
References 7 publications
4
130
0
5
Order By: Relevance
“…Long‐term complaints after caesarean section, such as postmenstrual spotting, dysmenorrhea, dyspareunia, or chronic pelvic pain, are frequently described in relation to the presence of a niche 1, 2, 3, 4, 5, 6, 7, 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term complaints after caesarean section, such as postmenstrual spotting, dysmenorrhea, dyspareunia, or chronic pelvic pain, are frequently described in relation to the presence of a niche 1, 2, 3, 4, 5, 6, 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…Two independent prospective cohort studies reported that the presence of a niche after caesarean section increases the risk of postmenstrual spotting for more than 2 days from 15 to 30% 1, 3. Postmenstrual spotting may be caused by a mechanical outflow problem, with the retention of menstrual blood in a niche,4, 5, 7, 8 or by the accumulation of blood because of impaired uterine contractions at the site of the niche 5. Additionally, newly formed fragile vessels in the niche may play a role in the formation of blood or fluid in the niche and uterine cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding or spotting after menstruation decreases the fertility due to changes in follicular-phase mucus quality, decreasing sperm motility in cervical canal or inhibiting implantation process [8]. Abnormal uterine spotting is probably caused by impaired contractility of muscle fibers surrounding the niche [5,9].…”
Section: Symptomsmentioning
confidence: 99%
“…In the seventies, hysterography had a major role in showing defective scarification (presence of scar niche), recently replaced by hysterosonography, hysteroscopy and magnetic resonance, also performed outside the gestational period. [7][8][9] Ultrasonography, a safe, noninvasive method, 10 has been used to that end during pregnancies since the eighties; 2;11 however, subjective assessment of the resulting ultrasonograms are a drawback, since visuals are not enough to determine the precise echogenicity of the tissues. Hence, quantitative and computerized analysis provided by gray-level histograms from an area of interest provide the opportunity to perform minute studies of uterine scars from previous Cesarean sections, since they enable us to compare the same region in different patients.…”
Section: Original Article Introductionmentioning
confidence: 99%